The Adaptability of Women Workers in the Higher Education Environment of Samarinda City to WFH Patterns during the Covid-19 Pandemic - Fajar Apriani; Aulia Suhesty (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The Covid-19 pandemic that has hit the world since December 2019 has changed the order of human life, including work patterns in public and private sector organizations in the context of implementing social distancing. This article analyzes the adaptability of workers to produce performance in their organizational environment under abnormal conditions (during a pandemic). Research subjects are female workers in the university environment of Samarinda City from four universities selected to be the sample, namely Mulawarman University, Muhammadiyah University of East Kalimantan, Samarinda State Islamic Institute and Samarinda State Polytechnic. The result showed that the application of the Work from Home (WFH) pattern faced by female workers in the Samarinda City university environment during the Covid-19 pandemic did not become an obstacle to their work productivity, due to high adaptability. Although WFH exposes female workers, especially those who are married and have children, to various challenges related to changes in their work environment during the pandemic period. So that the higher the adaptability of female workers in the university environment in Samarinda City, the higher their work productivity will also increase during the WFH pattern during the Covid-19 pandemic. The WFH patterns become a new form of work model that can increase work productivity and improve the quality of life of female workers in the university environment in Samarinda City, because the role of the public and the domestic role it carries is still capable of being done. Abstrak: Pandemi Covid-19 yang melanda dunia sejak Desember 2019 merubah tatanan kehidupan manusia, termasuk pola kerja di lingkungan organisasi sektor publik maupun swasta dalam rangka penerapan social distancing. Artikel ini menganalisis adaptabilitas pekerja dalam menghasilkan kinerja di lingkungan organisasinya pada kondisi tidak normal (masa pandemi). Subyek penelitian adalah para pekerja perempuan di lingkungan perguruan tinggi Kota Samarinda dari empat perguruan tinggi yang terpilih menjadi sampel yaitu Universitas Mulawarman, Universitas Muhammadiyah Kalimantan Timur, Institut Agama Islam Negeri Samarinda dan Politeknik Negeri Samarinda. Hasil penelitian menunjukkan bahwa penerapan pola WFH yang dihadapi pekerja perempuan di lingkungan perguruan tinggi Kota Samarinda selama masa pandemi Covid-19 tidak menjadi hambatan bagi produktivitas kerja mereka, sebab adanya adaptabilitas yang tinggi. Walaupun WFH menghadapkan pekerja perempuan, khususnya yang berstatus menikah dan memiliki anak, pada berbagai tantangan yang berkaitan dengan perubahan lingkungan kerjanya selama masa pandemi. Sehingga semakin tinggi adaptabilitas pekerja perempuan di lingkungan perguruan tinggi Kota Samarinda, maka semakin meningkat pula produktivitas kerjanya selama pola WFH di masa pandemi Covid-19. Pola WFH menjadi bentuk model kerja baru yang mampu meningkatkan produktivitas kerja serta meningkatkan kualitas kehidupan pekerja perempuan di lingkungan perguruan tinggi Kota Samarinda, sebab peran publik dan peran domestik yang diemban tetap mampu dilakukan.